Registration of 'Otto' Wheat. Issue 2 (2nd April 2013) - Carter, A. H.; Jones, S. S.; Lyon, S. R.; Balow, K. A.; Shelton, G. B.; Higginbotham, R. W.; Chen, X. M.; Engle, D. A.; Baik, B.; Guy, S. O.; Murray, T. D.; Morris, C. F.
Abstract : Resistance to strawbreaker foot rot (caused by Oculimacula yallundae Crous & W. Gams and O. acuformis Crous & W. Gams) and to stripe rust (caused by Puccinia striiformis Westend. f. sp. tritici Eriks.) are important traits for winter wheat cultivars produced in the Pacific Northwest region of the United States. The objective of this research was to develop an adapted winter wheat cultivar with highly effective resistance to both diseases. 'Otto' (Reg. No. CV‐1087, PI 667557) soft white winter wheat ( Triticum aestivum L.) was developed and released in September 2011 by the Agricultural Research Center of Washington State University. Otto was tested under the experimental designations J980218, J980218‐6, and WA008092, which were assigned through progressive generations of advancement. Otto is a semidwarf cultivar adapted to the low rainfall (<300 mm of average annual precipitation), unirrigated wheat production regions of Washington. Otto is resistant to strawbreaker foot rot, has high‐temperature, adult‐plant resistance to the stripe rust pathogen, is tolerant to both speckled (caused by Typhula ishikariensis S. Imai) and pink [caused by Microdochium nivale (Fr.:Fr.) Samuels & I. C. Hallett] snow molds, is intermediate in height, has midseason maturity, and has a high test weight and grain yield potential. Otto has end‐use quality properties similar or superior to those of 'Stephens', 'Brundage 96', and 'Xerpha'.